2016
DOI: 10.1590/s0102-865020160020000003
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve identification with fluorescent dye in rats

Abstract: PURPOSE:The parotidectomy technique still has an elevated paresis and paralysis index, lowering patient life's quality. The correct identification of the facial nerve can prevent nerve damage. Fluorescent dye identifies nerves in experimental studies but only few articles focused its use on facial nerve study in parotidectomies. We aimed to stain the rat facial nerve with fluorescent dye to facilitate visualization and dissection in order to prevent injuries. METHODS:Forty adult male Wistar rats were submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Prior studies in surgical fluorescent imaging have focused primarily upon the preservation of nerves and utilize contrast agents with varying nerve specificity 9 . For instance, a number of nerve-specific contrast agents have been developed, such as 4,4′-[(2-methoxy-1,4-phenylene)de-(1E)-2,1-ethenediyl]bis-benzenamine (BMB) and 4-[(1E)-2-[4-[(1E)-2-[4-aminophenyl]ethenyl]-3-methoxyphenyl]ethenyl]-benzonitrile (GE3082) which have been shown to help identify the sciatic nerve in porcine models as well as brachial plexus, sciatic, and trigeminal ganglia in rats 14 , 15 , 16 . The DOCI system does not require the use of contrast media as it is based upon the detection of fluorescence decay rates of endogenous fluorophores and thus avoids any potential toxicities that may be associated with labeling agents.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in surgical fluorescent imaging have focused primarily upon the preservation of nerves and utilize contrast agents with varying nerve specificity 9 . For instance, a number of nerve-specific contrast agents have been developed, such as 4,4′-[(2-methoxy-1,4-phenylene)de-(1E)-2,1-ethenediyl]bis-benzenamine (BMB) and 4-[(1E)-2-[4-[(1E)-2-[4-aminophenyl]ethenyl]-3-methoxyphenyl]ethenyl]-benzonitrile (GE3082) which have been shown to help identify the sciatic nerve in porcine models as well as brachial plexus, sciatic, and trigeminal ganglia in rats 14 , 15 , 16 . The DOCI system does not require the use of contrast media as it is based upon the detection of fluorescence decay rates of endogenous fluorophores and thus avoids any potential toxicities that may be associated with labeling agents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fluorescent agents can accumulate in peripheral nerve tissue through free diffusion and active reuptake ( Schmued, 2016 ). By observing the timing and metabolic characteristics of fluorescent dyes in various tissues in vivo , we can effectively visualize nerve tissue intraoperatively ( de Melo et al, 2016 ; Debie and Hernot, 2019 ; Walsh et al, 2019 ).…”
Section: Neuro-nonspecific Agentsmentioning
confidence: 99%
“…The results showed that carbon flower fluorescent agents had a strong fluorescence effect and that neurotoxicity was only apparent in cases of temporary paralysis ( Dogru et al, 2008 ). The use of FastDio also made the facial nerves detectable under white light illumination ( de Melo et al, 2016 ). This agent labeling is compatible with nerve survival and function.…”
Section: Neuro-nonspecific Agentsmentioning
confidence: 99%
“…The use of fluorescent dyes has been shown to significantly improve intraoperative identification and preservation of the facial nerve during parotidectomy in both murine and rat models. 88,89 An injectable fluorescently labeled nerve binding probe, F-NP41, was also shown to aide in intraoperative visualization of transected facial nerves in a mouse model that had been denervated up to 9 months and decrease the amount of time required for nerve identification by 40% compared to surgeries performed under white light. 90 The potential for fluorescence guided surgery to improve surgical outcomes has subsequently been validated in humans and is currently being investigated in a multi-institutional phase I clinical trial of head and neck cancer patients.…”
Section: Use Of Fluorescent Dyes For Nerve Identificationmentioning
confidence: 99%